Molecular level comparison of water extractives of maple and oak with negative and positive ion ESI FT‐ICR mass spectrometry. (29th July 2019) - He, Zhongqi; Sleighter, Rachel L.; Hatcher, Patrick G.; Liu, Shasha; Wu, Fengchang; Zou, Haixuan; Olanya, O. Modesto
Abstract: Soluble extractives in wood function to protect living trees from destructive agents and also contribute to wood color and fragrance. Some extractive components have biological activities with medical applications. They also play important roles in wood processing and related applications. To increase the knowledge of wood chemistry, maple and oak were extracted by water. Ultraviolet/visible (UV/vis) spectroscopy indicated the presence of a phenolic compound, resorcinol, in maple extractives having higher molecular mass and more aromatic components than oak extractives. Negative and positive electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI FT‐ICR‐MS) identified thousands of formulas in the two samples in the m/z range of 200 to 800. They mainly fall into the lignin‐like, carbohydrate‐like, and tannin‐like compound categories. The top 25 peaks (ie, formulas) with the highest relative magnitude in negative ESI represented nearly 50% of the summed total spectral magnitude of all formulas assigned in the maple and oak extractives. Furthermore, the base peak (ie, most abundant peak) accounted for about 14% of the total abundance in each wood sample. Literature comparisons identified 17 of 20 formulas in the top five peaks of the four spectra as specific bioactive compounds in trees and other plants, implying the potential to explore utilization of maple and oak extractives for functional and medicinal applications. The various profiling of the top 25 peaks from the two samples also suggested the possible application of FT‐ICR‐MS for detecting chemical markers useful in profiling and identification of wood types and sources.